Model For Forming Personal Branding For Students At Madrasah Aliyah Model Zainul Hasan Genggong Probolinggo - Nur Fatimah; Unzilatul Rahmah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
In this era of intense job competition, every individual needs to have the ability to showcase their potential. Personal branding is a way to show oneself in society in a positive way. This research is a qualitative study which aims to analyze the model for forming students' personal branding at the Zainul Hasan Genggong Model Madrasah Aliyah. This madrasa was chosen because this madrasa is one of the madrasas that implements the Semester credit system, one of the educational institutions under the auspices of the Zainul Hasan Islamic Boarding School Foundation with the largest number of students, and has alumni spread across various well-known universities at home and abroad. From this research, it was found that the formation of student personal branding at the Zainul Hasan Genggong Model Madrasah was carried out by finding student ambitions, evaluating student self-evaluation, determining student personal branding and strengthening student personal branding. The formation of students' personal branding is carried out in extracurricular activities and superior programs at the madrasah.